Algorithms for Simulation of Shunt Currents in a Vanadium Redox Flow Battery - Decebal Aitor Ispas-Gil; Ekaitz Zulueta; Javier Olarte; Jose Manuel Lopez-Guede (Algorithms)
This paper presents an algorithm for the implementation of a model that calculates shunt currents in redox flow batteries. The formation patterns of the equivalent electrical circuit that models shunt currents in redox flow batteries are analyzed in such a way that the proposed algorithm is applicable for batteries with any number of cell stacks and any number of cells per stack. Linear algebra is applied to solve the equation system related to the equivalent electric circuit. The solution of such a system of equations is obtained by performing the inverse of a matrix and premultiplying that matrix on both sides of the equation system. This being rather trivial, the real problem lies in automating the generation of the matrices relative to the system of equations. For this reason, it is analyzed how to generate the matrixes in order to facilitate the implementation of their generation. Finally, the most important parts of the implementation of the resolution algorithm are shown.